Kainan na! a mediated dinner with the family - Cielo, John Dave C.
This thesis is about the contemplation of feelings of solitude, disconnect and belongingness anchored in the concept of familial relations. It is primarily motivated by my experience of leaving home at the early age of twelve and how mu childhood dependency was brought to an early halt. This project is a visual representation of the family tied the concept of the hapagkainan as a place to connect. The work is a five-part video projection of individual portraits of my entire family apart from myself while eating. This series will be projected in an open wall to be viewed on a table and chair setup reminiscent of a dining table. This thesis, in its essence, is a metaphorical attempt to reunite with the family.